Barriers of Appropriate Antibiotic Prescription at PHCC in Qatar: Perspective of Physicians and Pharmacists - Nahla Sharaf; Ghadir Fakhri Al-Jayyousi; Eman Radwan; Shimous Mohamed Elamin Shams Eldin; Dhouha Hamdani; Huda Al-Katheeri; Khalid Elawad; Anjum Habib Sair (MDPI AG, 2021)
The Ministry of Public Health in Qatar developed the NAP (National Action Plan to combat Antimicrobial Resistance (AMR) in collaboration with WHO Regional Office for the Eastern Mediterranean (WHO/EMRO). Among the major factors shaping AMR is antimicrobial prescribing and use. Tailoring Antimicrobial Resistance Program is a behavior change methodology that is utilized to adapt behavior change in relation to antimicrobial use. This study explores barriers of appropriate antibiotic (AB) prescription from the physicians' and pharmacists' perspectives at primary healthcare centers in Qatar. Data were collected from 50 participants across two PHCCs: 30 physicians and 20 pharmacists. Two different interview guides were constructed: One for physicians and one for pharmacists. In-depth, face-to-face, five focus groups were conducted and transcribed verbatim. Inductive qualitative analysis, involving discovering the themes in the interviews, was followed. Data were analyzed using constant comparative techniques. The Major themes arose from the analysis revealed that patients, practitioners mainly physicians, and the organization itself, played a role in shaping these barriers in the two primary healthcare centers. The findings would help develop and pilot behavior change interventions among patients, physicians and pharmacists with the aim of optimizing appropriate antibiotic prescription and use, which would support the implementation of the antibiotic stewardship program. Effective behavior change interventions should consider multiple factors including individual and organizational factors to optimize appropriate antibiotic prescription.